Faktor – Faktor Yang Mempengaruhi Kinerja Manajemen Hotel ITDC Dalam Memanfaatkan Peningkatan Hunian Selama Presidensi G20 Tahun 2022 Di Bali - Komang Ayulinia Dewi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The title of this thesis is "Factors Affecting the Performance of ITDC Hotel Management in Taking Advantage of Occupancy Improvements During the 2022 G20 Presidency in Bali". international world, so it is expected to be able to help move the Indonesian economy towards the performance of employees at hotels in the ITDC Nusa Dua Bali area. This research is quantitative research. The population taken in this study were all employees of the hotel in the area of Nusa dua Bali, with as many as 321 employees. Methods of collecting data using a questionnaire, and document search. Data analysis was carried out by regression test multiple linear. Before performing multiple linear regression analysis, the first classical assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test. Results research shows that ability and expertise, leadership, and management performance simultaneously have a positive and significant effect on employee performance at hotels in the ITCD Nusa Dua area., abilities and expertise have a positive and significant effect on management performance at hotels. significant impact on management performance at hotels in the ITCD Nusa Dua area.